PENGARUH PERSEPSI MASYARAKAT TERHADAP KUALITAS PELAYANAN PADA PT. KARAMPUANG MULTI DAYA DI KABUPATEN MAMUJU - Nurfadila, Nurfadila; Rasyid, Rohsita Amalyah (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2024)
Multi-Power Village in Mamuju District . The research method used is by using de quantitative method with primary data using a questionnaire. Respondents in the study were all customers at PT. Karampuang Multi Daya in Mamuju Muju Regency with a total population of 800 customers, the sample used was the Nonprobability Sampling technique, and the number of samples was determined using the slovin formula with a sample size of 89 respondents. The formula in this study uses, validity test, reliability test, multiple linear regression, t test and coefficient of determination test. The results in this study indicate that public perception (X) has a partially significant effect on service quality (Y) at PT. Multi Daya Karampuang in Mamuju Regency and public perception (X) has a correlation with service quality (Y) at PT. Multi-Power Village in Mamuju District.